Facilitating EFL Students in Maintaining Flow of Talks Using Mind Mapping - Abdul Halim (Langkawi: Journal of The Association for Arabic and English, 2022)
This case study discussed the use of mind mapping in sustaining the EFL students’ flow of talks. Mind mapping was utilized to assist the participants in generating ideas, retaining vocabulary, making notes and tasks, and providing clear progress for presentations or talks. After mind mapping was introduced, the participants were asked to talk. They were also interviewed to obtain their general sense of how much mind mapping has contributed to maintaining the flow of their talks. These data were then analyzed qualitatively through the following stages: familiarizing with the data; generating initial codes; searching for themes; reviewing themes; defining and naming themes, and producing the report. The findings revealed that participants could sustain the entire talk, particularly the introduction and body as opposed to the conclusion. As for the conclusion, one did not use it at all in the first and second talks. This was primarily because such a student has a poor cognition process. Since mind mapping has had profound benefits to the target learners and the teachers, such as it could aid the desire to read, and uplift the competence of generating and organizing ideas. Explore its application in the teaching and learning process to maintain the flow of the talks is highly recommended.